Edukasi Kesadaran Siswa Tentang Dampak Negatif Makanan Cepat Saji Terhadap Kesehatan Anak - Zainal Munir; Ghifari Hiban Ashfihani; Aldo Jaiz Maulana Hidayatullah; Bintang Utama Putra; Fikri Aldi Maulana (Transformative Service Journal, 2025)
This Community Service Program was conducted for two months at MI Nurul Mun’im, focusing on nutrition education about fast food, which generally contains low nutritional value but high levels of saturated fats, sugars, salt, and calories. These components can trigger various health problems such as obesity, type 2 diabetes, hypertension, and other metabolic disorders. The low awareness among students regarding the long-term dangers of consuming such foods served as the main background for the importance of systematic nutrition education. The objective of this program was to improve students’ knowledge and awareness of the negative impacts of fast food consumption and to encourage the development of healthy eating habits from an early age. The implementation methods included interactive lectures, educational video screenings, quiz games, small group discussions, and the distribution of printed educational materials. The target participants were fifth- and sixth-grade students of MI Nurul Mun’im, totaling 70 students. The evaluation results showed that students gained a better understanding of fast food and the distinction between healthy and unhealthy foods. There was also an increase in their awareness of the dangers of fast food and their interest in adopting healthier eating patterns. The students’ enthusiasm during the Community Service activities brought many benefits both to the students and the school. Therefore, future long-term initiatives will focus on reducing fast food availability in the school canteen and providing quarterly mentoring sessions to update knowledge about healthy food.